Horizontal bone‐augmentation procedures in implant dentistry: prosthetically guided regeneration - Chiapasco, Matteo; Casentini, Paolo (Periodontology 2000, 2018)
The rehabilitation of partially or totally edentulous patients with implant‐supported prostheses has become routine, with excellent long‐term outcome. A proper implant position is mandatory to achieve good functional and esthetic outcome and may require an adequate amount of alveolar bone and surrounding soft tissue. When this is lacking because of atrophy, sequelae of periodontal disease, traumas or congenital malformations, increased bone volume and/or keratinized mucosa can be obtained by guided bone regeneration, bone‐grafting techniques and alveolar bone expansion. This article presents an evidence‐based, prosthetically driven approach for the treatment of edentulous ridges with horizontal defects. The classification of bony defects, the main augmentation techniques, the selection criteria among different surgical procedures for different types of bony defects, and the advantages, disadvantages and limitations of each technique, are described in detail.